A locus conferring tolerance to Theileria infection in African cattle - Wragg, D.; Cook, Elizabeth A.J.; Latré de Laté, Perle; Sitt, Tatjana; Hemmink, Johanneke D.; Chepkwony, Maurine C.; Njeru, Regina; Poole, Elizabeth J.; Powell, J.; Paxton, E.A.; Callaby, R.; Talenti, A.; et al. (2022)
East Coast fever, a tick-borne cattle disease caused by the Theileria parva parasite, is among the biggest natural killers of cattle in East Africa, leading to over 1 million deaths annually. Here we report on the genetic analysis of a cohort of Bos indicus (Boran) cattle demonstrating heritable tolerance to infection with T. parva (h2 = 0.65, s.e. 0.57). Through a linkage analysis we identify a 6 Mb genomic region on bovine chromosome 15 that is significantly associated with survival outcome following T. parva exposure. Testing this locus in an independent cohort of animals replicates this association with survival following T. parva infection. A stop gained variant in a paralogue of the FAF1 gene in this region was found to be highly associated with survival across both related and unrelated animals, with only one of the 20 homozygote carriers (T/T) of this change succumbing to the disease in contrast to 44 out of 97 animals homozygote for the reference allele (C/C). Consequently, we present a genetic locus linked to tolerance of one of Africa’s most important cattle diseases, raising the promise of marker-assisted selection for cattle that are less susceptible to infection by T. parva.